2019
DOI: 10.1080/21691401.2019.1576706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graphene oxide and graphene oxide quantum dots on the osteogenic differentiation of stem cells from human exfoliated deciduous teeth

Abstract: Graphene and its derivatives, graphene oxide (GO) and graphene oxide quantum dots (GOQDs), have recently attracted much attention as bioactive factors in differentiating stem cells towards osteoblastic lineage. The stem cells from human exfoliated deciduous teeth (SHEDs) possess the properties of selfrenewal, extensive proliferation, and multiple differentiation potential, and have gradually become one of the most promising mesenchymal stem cells (MSCs) in bone tissue engineering. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
(84 reference statements)
0
24
0
Order By: Relevance
“…Thus, systematic studies that focus on the relationships of various parameters (i.e., the surface functionalities, sizes, surface charges, shapes, dimensions, mechanical strength, etc.) and their effects on promoting cell proliferation and osteogenic differentiation would be highly desired; and this type of study would provide invaluable insights for the rational design of innovative carbon‐based nanomaterial BTE scaffolds …”
Section: Resultsmentioning
confidence: 99%
“…Thus, systematic studies that focus on the relationships of various parameters (i.e., the surface functionalities, sizes, surface charges, shapes, dimensions, mechanical strength, etc.) and their effects on promoting cell proliferation and osteogenic differentiation would be highly desired; and this type of study would provide invaluable insights for the rational design of innovative carbon‐based nanomaterial BTE scaffolds …”
Section: Resultsmentioning
confidence: 99%
“…Stem cells from different sources could be used as progenitor cells in the process of bone formation, so their recruitment and osteogenic differentiation were key factors for effective bone regeneration. GDs were proved to have the ability of osteogenic induction, [144][145][146][147][148][149][150][151][152] as shown in Table 4. In this subsection, the signaling pathways involved in GDs-induced bone regeneration were discussed, including which signaling pathways of osteogenic differentiation of stem cells from different sources were affected by GDs and the effect of GDsrelated parameters on the signaling pathway.…”
Section: Mechanism Of Gds-induced Bone Regeneration Possible Signalinmentioning
confidence: 99%
“…They demonstrated that GQDs enhanced alkaline phosphatase activity and expression of several osteogenic markers in the stem cells. In a recent study, Yang et al 56 studied and compared the effect of GO and GQDs on the osteogenic differentiation of human stem cells sourced from exfoliated deciduous teeth (SHEDs). The uptake of GQDs by the SHEDs and their cytoplasmic distribution were confirmed using the fluorescent property of GQDs.…”
Section: Interaction With Stem Cellsmentioning
confidence: 99%